Alpha‐Linolenic Acid and Mortality Among Adults With Type 2 Diabetes: Findings From Two National Cohorts - Boyang Chen; Qi Wu; Sibo Liu; Hongkun Di; Wen Hu; Tianzhu Qin; Yushuang Wang; Rong Chen; Han Wang; Ying Chen; Xiang Cheng; Jiawei Yin; et al. (Journal of Diabetes, 2025)
ABSTRACT Background Dietary alpha‐linolenic acid (ALA) regulates lipid metabolism and insulin sensitivity, but few studies have investigated the association between ALA and the risk of mortality among adults with type 2 diabetes (T2D). This study examines whether increasing dietary ALA intake contributes to the long‐term survival of adults with T2D. Methods This cohort study included 9603 participants with T2D, including 7953 adults from the National Health and Nutrition Examination Survey (NHANES; 1999–2018) and 1650 adults from the China Health and Nutrition Survey (CHNS; 1997–2011). Dietary information was collected through 24‐h dietary recalls. Cox proportional hazards regression was employed to estimate hazard ratios (HRs) and 95% CIs for mortality from all‐cause and cardiovascular disease (CVD). Results During 75 535 person‐years of follow‐up, a total of 2468 deaths were documented. After multivariate adjustment, the pooled HRs (95% CIs) of all‐cause mortality were 1.00, 0.87 (0.76–0.99), and 0.79 (0.67–0.94) across tertiles of ALA (ptrend = 0.01). There was a linear inverse relationship between ALA intake and all‐cause mortality, demonstrating a 9% (HR: 0.91;95% CI: 0.85_0.97) lower risk of all‐cause mortality with each 1 g/day increase of dietary ALA intake in the pooled analysis (pnonlinear > 0.05). In addition, ALA intake was inversely associated with CVD mortality, and HR comparing the highest with the lowest tertile was 0.68 (0.50–0.91; ptrend = 0.01). Consistent results were observed in both the stratified and sensitivity analyses. Conclusions Higher dietary ALA intake was associated with a lower risk of all‐cause and CVD mortality among adults with T2D.